Level of knowledge about healthy feeding and grade of acceptability of the menus in the feeding service by the resident students in a private University in Lima, 2016 - Aguirre Paredes, Zulma Elisa (2019)
Objective: Determine the relationship of the level of knowledge about healthy feeding and grade ofacceptability of the menus in the feeding service by the resident students in a private University inLima, 2016. Materials and Methods: The type of study is descriptive, correlational cross-section.The sample was comprised of 268 students selected by sampling non-probability of intentional type.The questionnaire was designed to measure the level of knowledge about healthy feeding with areliability of 0.732, and the second to measure the degree of acceptability of menus with a reliabilityof 0.926, applied to university students of the food service during a week. Results: They show thatit doesn’t exist a significant relationship statistically between the level of knowledge about healthyfeeding and degree of acceptability of the menus offered by the feeding service in a private Universityin Lima (p=0,300). According with the level of knowledge about healthy feeding 53.4% has a regularlevel and only 43.3%a high level. In the other hand, the 56% has a good degree of acceptability of theoffered menus. As a conclusion, it doesn’t exist a significant correlation statistically between the level ofknowledge about healthy feeding and the degree of acceptability in the menus of the Feeding Service.